Respuesta :

TSO
[tex]3j - [2k - [5h - (3j + k)]]\\\\3j -[2k-[5h-3j-k]]\\\\3j-[2k-5h+3j+k]\\\\3j-[3k-5h+3j]\\\\3j-3k+5h-3j\\\\-3k+5h\\\\\boxed{\bf{5h-3k}}[/tex]

Answer:

The given expression [tex]3j-\{2k-[5h-(3j+k)]\}[/tex] is [tex]5h-3k[/tex]

Step-by-step explanation:

Given expression, [tex]3j - \{2k - [5h - (3j + k)]\}[/tex]

We are required to simplify the above expression.

Consider the given expression, [tex]3j - \{2k - [5h - (3j + k)]\}[/tex]

Removing brackets one by one,

Firts we remove round brackets, we get,

[tex]\Rightarrow 3j - \{2k - [5h - (3j + k)]\}=3j-\{2k-[5h-3j-k]\}[/tex]

Again removing square brackets, we get,

[tex]\Rightarrow 3j-\{2k-[5h-3j-k]\}=3j-\{2k-5h+3j+k\}[/tex]

Now removing curly brackets, we get,

[tex]\Rightarrow 3j-2k+5h-3j-k[/tex]

Now solving , we get,

[tex]\Rightarrow 3j-2k+5h-3j-k=-3k+5h[/tex]

Thus, the given expression [tex]3j-\{2k-[5h-(3j+k)]\}[/tex] is [tex]5h-3k[/tex]